Performance Analysis Of Fuel Oil Purifier Filtration Process On Ships MV. TANTO LUAS - Irwan Irwan; Chairul Insani Ilham; Fitradi Geraldo Ardinof Pratama Putra (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Fuel oil purifier on board is one of the auxiliary aircraft that plays an important role in separating fuel from water and dirt. The use of clean fuel is to support the operation of the main engine in producing complete combustion. Therefore, it is necessary to analyze the problems that may occur with the performance process of the F.O purifier such as the abnormality of the Fuel Oil filtration process on the F.O purifier to anticipate the influence that arises if this aircraft has problems cleaning the fuel from liquid and solid impurities. This research was carried out on board the MV. TANTO LUAS fleet owned by pt. TANTO INTIM LINE, which was carried out for approximately 9 months. The data collection method used in this research is the observation method (observation research method). Primary data here are obtained from direct observations and secondary data are obtained from documents and literature related to this study. The results obtained from this study show that damage occurs and improper installation of the gravity disc can adversely affect the performance of the purifier. This is characterized by the abnormality of the F.O pufirier purification process which results in unclean fuel being wasted out and accommodated in the sludge tank. The corresponding temperature is 85°C and viscosity is 37.8°C (100°F).